Effect of QR code and mobile money on performance of SMEs in developing countries. The role of dynamic capabilities - Klenam Korbla Ledi; Enya Ameza-Xemalordzo; George Kofi Amoako; Bernice Asamoah (Cogent Business & Management, 2023)
The purpose of the study is to examine the effect of QR code payment and mobile money on the performance of SMES in developing countries and the moderating role of dynamic capabilities. A survey method was used to gather data from the target population of SMEs that are making use of digital financial services in their business transactions. A total of 206 SMEs responded to the questionnaires. The study found that both mobile money usage and QR code payments have a significant and positive impact on SME performance. In addition to that, the study revealed that the effect of dynamic capabilities on firm performance was also statistically significant. The study also found the moderating effect was statistically significant for mobile money payments. However, for QR code payments, the moderation effect was not statistically significant. These findings imply that it is prudent for SMEs to adopt digital financial services for business transactions. Thus, improvement in the level of innovativeness in a dynamic business environment plagued by the COVID-19 pandemic will significantly improve SME performance. This will help make SMEs more robust and adjust themselves to the dynamics of the business environment.
Keywords: 650; COVID-19; dynamic capability; firm performance; mobile money; QR code; SMEs